PENGARUH CITRA MEREK, HARGA, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SEPATU MEREK REEBOK (STUDI KASUS PADA MAHASISWA/I FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS WIJAYA KUSUMA SURABAYA) - Afrizal Rifqi Zaky Pramudya; Arochman, Maqbula (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Business competition in shoe products has experienced very rapid development in the current era, many shoe brand products have emerged and competed in the market. Reebok is one of the many brands used by consumers as one of their favorite shoe favorites. Therefore, this study is entitled